The irrigation efficiency trap: rational farm-scale decisions can lead to poor hydrologic outcomes at the basin scale - Morrisett, Christina N.; Van Kirk, Robert W.; Bernier, London O.; Holt, Andrea L.; Perel, Chloe B.; Null, Sarah E. (Frontiers in Environmental Science, 2023)
Agricultural irrigation practices have changed through time as technology has enabled more efficient conveyance and application. In some agricultural regions, irrigation can contribute to incidental aquifer recharge important for groundwater return flows to streams. The Henrys Fork Snake River, Idaho (USA) overlies a portion of the Eastern Snake Plain Aquifer, where irrigated agriculture has occurred for over a century. Using irrigator interviews, aerial and satellite imagery, and statistical streamflow analysis, we document the impact of farm-scale decisions on basin-scale hydrology. Motivated to improve economic efficiency, irrigators began converting from surface to center-pivot sprinkler irrigation in the 1950s, with rapid adoption of center-pivot sprinklers through 2000. Between 1978–2000 and 2001–2022, annual surface-water diversion decreased by 311 Mm3 (23%) and annual return flow to the river decreased by 299 Mm3 over the same period. Some reaches that gained water during 1978–2000 lost water to the aquifer during the later period. We use an interdisciplinary approach to demonstrate how individual farm-scale improvements in irrigation efficiency can cumulatively affect hydrology at the landscape-scale and alter groundwater-surface water relationships. Return flows are an important part of basin hydrology in irrigated landscapes and we discuss how managed and incidental aquifer recharge can be implemented to recover return flows to rivers.